REFRAKTURASI PADA MALUNION FRAKTUR MANDIBULA DENGAN PENDEKATAN INTRAORAL (LAPORAN KASUS) - Cristiani Nadya Pramasari (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Untreated mandibular fractures could lead to malocclusion. This condition can affect a patient’s Oral Health-related Quality of Life. Case and Management: A 20 years old woman visited the Dental Clinic Specialist, RSUD A.W. Sjahranie Samarinda with complaints of difficulty when chewing that lasted for the last 3 months. Previously the patient had an accident and had never been treated. The patient was then referred and underwent refracturing and ORIF with the intraoral approach as the management of mandibular fractures malunion. Conclusion: Untreated mandibular fractures caused malocclusion of the teeth. Refracturing and ORIF with an intraoral approach gave optimal and satisfactory results.